Implementation of Health and Safety Management Systems in Construction Projects in Jigawa State, Nigeria: Barriers and Mitigation Measures - Isa Haruna (INTERNATIONAL JOURNAL OF ENGINEERING AND MODERN TECHNOLOGY, 2026)
Construction remains a critical driver of socio-economic development but continues to be characterised by persistent health and safety failures, particularly in developing contexts. In Jigawa State, Nigeria, HSMS implementation has remained largely ineffective due to systemic organisational, managerial, and institutional constraints. Accordingly, this study aimed to empirically examine the barriers to HSMS implementation and identify context-specific mitigation measures in the construction sector. Using a quantitative cross-sectional survey design, data were collected from construction professionals through structured questionnaires and analysed using descriptive statistics and Relative Importance Index (RII). The results indicate that inadequate worker training, weak management commitment, absence of organisational safety policies, insufficient PPE, and worker negligence ranked highest as barriers (RII = 0.875), while key mitigation measures included behavioural feedback mechanisms (RII = 0.875), senior management commitment (RII = 0.850), and structured worker observation (RII = 0.825). In conclusion, HSMS failure is fundamentally systemic rather than technical; therefore, coordinated leadership-driven, regulatory, and organisational reforms are recommended to embed HSMS as a functional governance system for sustainable construction safety performance.